Liver transplantation: a 10-year single center experience in Pernambuco- northeastern Brazil - Miranda, Luiz Eduardo C. (2010)
Purpose: The aim of this study is to analyze a ten-year single center experience in liver transplantation in Pernambuco - Northeastern region of Brazil. Methods: Data were retrospectively collected from medical records of 302 patients who underwent Orthotopic Liver Transplantation (OLT) between 1998 and 2008 at Oswaldo Cruz University Hospital, Pernambuco – Brazil. We analyzed just the outcomes and survival curve of 195 adult liver transplantation recipients from deceased donor. Results: Data concern liver donor, surgery technical aspects and liver transplantation recipients’ postoperative evolution are presented and discussed. This center has a significant experience in liver transplantation using conventional technique with no venovenous bypass. Efficient management of liver transplantation practice has made it feasible to keep the cold ischemia time within 6-7 hours. Because of the organ shortage, we have used a large amount of extended criteria liver donor. The survival 1-year rata was 76.4%. Conclusion: It is possible to provide a high-quality public medical assistance in an efficient and continuous manner in less developed areas of Brazil.